Pengaruh Investment Opportunity Set (IOS), Kebijakan Dividen, Dan Opportunistic Behavior Terhadap Nilai Perusahaan - Rika Amanda Amanda Putri; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2019)
The purposeof this study was to examine the effect of Investement Opportunity Set (IOS), dividend policy, and opportunistic behavior on firm value at Manufacturing Companies listed on Stock Exchange in 2015-2018. This study used secondary data from the company’s annual report. The samplimg method in this study used purposive sampling, the final sample obtained was 29 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. The analysis in this study used multiple linear regression analysis. The results showed that the Investment Opportunity Set (IOS) used price proxy (MBVE) and investment proxy (CAPBVA) have a significant positive effect on firm value, while the dividen policy and opportunistic behavior have a negative effect on firm value but not significant.